Interdependence Between River Aquifer Groundwater Flow and Temperature–Depth Profiles: Type Curves Based on Pi Theorem and Numerical Simulations - José Antonio Jiménez-Valera; Iván Alhama; Carlos Duque; David Labat (Applied Sciences)
The interaction between surface water and groundwater has been extensively studied due to its water management implications and the potential environmental impacts arising from it. Experimental studies and numerical modeling have supported analytical solutions; these solutions have been proposed for specific cases in which the aim has been to understand discharge/recharge and aquifer characterization. In this study, new graphical solutions or type curves are provided to estimate the subsurface flow and thermal–mechanical parameters in anisotropic porous media. Using the non-dimensionalization technique of the governing equations, new dimensionless groups (lumped parameters) that govern the solution of both the mechanical problem (uncoupled) and the thermal problem are obtained. From these groups, and by applying the pi theorem and examining numerical simulations of numerous cases, user-friendly type curves are obtained. The recharge flow and hydraulic conductivity are calculated when the thermal properties, geometrical parameters, and temperature variables are known. To evaluate the reliability of the type curves, two real case studies are presented: the interaction between the Guadalfeo River and the Motril-Salobreña coastal aquifer, and the artificial recharge program in the coastal aquifer of Agua Amarga in southern Spain. For verification, the groundwater flow obtained from the type curves is compared with the recharge data. In the case of the river–aquifer interaction, the recharge flow obtained is 13% less than that estimated in previous studies. Regarding the artificial recharge of the coastal aquifer, the flow obtained is 21% less than the volume irrigated over the salt marsh. The uncertainties related to hydrogeological features are considered to have the greatest influence on the error.